Development of Physics Learning Media Assisted by Scratch Simulation for Parabolic Motion Material - Faradila, Adinda Septi Zalza; Perdana, Riki (Jurnal Pendidikan dan Ilmu Fisika, 2024)
The subject of physics is considered challenging by some students due to its abstract concepts, which can make the learning process difficult. This research aims to develop animated videos using Scratch software to assist students in dealing with difficulties in understanding the concept of projectile motion. The research method employed is Research and Development (R&D), utilizing the ADDIE model. Data analysis involves descriptive analysis techniques, calculating the percentage of validation scores. Results from the evaluation by two physics education experts indicate that the content validity of the media is excellent at 92% without any modifications, and the presentation validity is at 88%. Based on these validation results, it can be concluded that the physics learning media assisted by Scratch simulations developed are suitable for use.